EFEKTIVITAS PENGGUNAAN MEDIA PIANIKA SEBAGAI PENINGKATAN KESADARAN NILAI BUDAYA PADA LAGU DAERAH - Hidayah, Aulia Nurul; Mayariah, Alya; Wijayanto, Wasis (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to determine the effectiveness of the use of piano musical instrument media in increasing students' awareness of local cultural values through regional songs, especially the song "Gundul-Gundul Pacul" in grade IV MI Khoiriyah Kayen Pati. The research uses a qualitative approach with a case study type. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The results of the study show that the use of the piano not only improves students' musical skills, but also fosters understanding of the cultural meaning contained in traditional songs. Students showed high enthusiasm in the learning process, as well as improved piano playing skills and understanding of values such as simplicity, responsibility, and leadership. These findings indicate that the media of piano musical instruments is an effective means of learning musical arts based on local culture as well as in supporting character education in elementary schools.